Impact of hypoalbuminemia on the prognosis of relapsed/refractory B‐cell lymphoma treated with axicabtagene ciloleucel. (15th April 2021) - Melody, Megan; Gandhi, Sangeetha; Rahman, Zaid Abdel; Lengerke‐Diaz, Paula; Gannon, Nicole; Rosenthal, Allison; Truong, Tuan; Novo, Mattia; Brandes, Eva; Lange, Gina; Estby, Breana; Johnston, Patrick; et al.
Abstract: Introduction: Hypoalbuminemia is a known adverse prognostic factor in lymphomas. Yet, it is unknown if axicabtagene ciloleucel (axi‐cel) overcomes the adverse prognostic impact of hypoalbuminemia in relapsed/refractory large B‐cell lymphoma. Methods: We conducted a retrospective analysis across three Mayo Clinic centers to assess the relationship of hypoalbuminemia (defined as a serum albumin (SA) levels ≤ 3.5 g/dL) on outcomes of patients treated with axi‐cel. Results: This analysis included 81 patients. Two patients had no available SA levels preceding axi‐cel infusion. Eighteen patients (22.8%) had hypoalbuminemia with a median SA of 3.3 g/dL. Patients with normal SA had a statistically higher ORR than those without hypoalbuminemia ( P = .018). There was no difference in 1‐year PFS and OS between the group with hypoalbuminemia and the group with normal SA levels (48% vs 49%, P = .81) and (74% vs 73%, P = .97), respectively. There was no difference in the severity or median duration of cytokine release syndrome or neurotoxicity between the two groups. Conclusion: Notwithstanding the limitations related to the relatively small sample size, axi‐cel therapy appears to overcome the adverse effect of hypoalbuminemia on OS and PFS. Large multicenter clinical studies are certainly needed to validate these findings.